2004
DOI: 10.1111/j.1467-9817.2004.00232.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of orthographic depth on reliance upon semantic context for oral reading in English and Hebrew

Abstract: This paper examines the relationship between orthographic depth and reliance upon context for oral reading in English and Hebrew. Research on context effects in English has indicated that the decoding ability of adequate readers is only minimally affected by context. The effect of context may be greater in Hebrew because of its deeper orthography – context may help readers phonologically and semantically disambiguate words whose letters do not provide enough information for grapheme‐to‐phoneme conversion. It i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 30 publications
(47 reference statements)
0
3
0
Order By: Relevance
“…Using this method for investigating the role of context in Hebrew among bilingual Hebrew-English college students, Benuck and Peverly (2004) hypothesized that context would be more influential in unpointed Hebrew owing to phonological ambiguity. They found that the same readers, when presented with parallel sentences in Hebrew and in English, relied significantly more on context to read words in Hebrew than in English.…”
Section: Phase 3: the Role Of Supralexical Context In Resolving Homograph Identity In Unpointed Textmentioning
confidence: 99%
“…Using this method for investigating the role of context in Hebrew among bilingual Hebrew-English college students, Benuck and Peverly (2004) hypothesized that context would be more influential in unpointed Hebrew owing to phonological ambiguity. They found that the same readers, when presented with parallel sentences in Hebrew and in English, relied significantly more on context to read words in Hebrew than in English.…”
Section: Phase 3: the Role Of Supralexical Context In Resolving Homograph Identity In Unpointed Textmentioning
confidence: 99%
“…From the third grade onwards, children are gradually exposed to unvowelled texts, where they become dependent on the orthographic, morphological, semantic and contextual cues to decode and spell without full phonological information (Ravid, ; Share & Levin, ). The unvowelled version of the Hebrew orthography would be considered to be an example of a deep orthography because accurate decoding is dependent on contextual as well as morphological information to compensate for the missing phonological information (Benuck & Peverly, ). The Hebrew‐speaking participants in the current study were all literate in both vowelled and unvowelled Hebrew.…”
Section: El1 and Efl Spelling Developmentmentioning
confidence: 99%
“…The choice of symbolization entails an equally important but perhaps less obvious choice about which orthographic depth is most suitable: shallow or deep? The relative depth of different orthographies has been a key concept in the linguistics of writing ever since it was first introduced by Katz and Feldman (1981, 1983) and it remains the focus of ongoing research (e.g., Benuck & Peverly, 2004; Caravolas, Lervåg, Defior, Málková, & Hulme, 2013; Snider, 2014; Ziegler et al, 2010). Some orthographies, such as Spanish, are relatively shallow, mostly maintaining a one to one phonographic correspondence; others, such as French, are much deeper, the link between speech and spelling being less obvious.…”
Section: Introductionmentioning
confidence: 99%